2014
DOI: 10.5588/ijtld.13.0732
|View full text |Cite
|
Sign up to set email alerts
|

Derivation of a tuberculosis screening rule for sub-Saharan African prisons

Abstract: Low BMI and HIV infection were the most robust predictors of TB in our inmates; chest pain was additionally retained in one model. BMI and HIV should be further evaluated as the basis for TB screening rules for inmates, with modification as needed to improve the performance of the rules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 0 publications
1
19
0
4
Order By: Relevance
“…Measures of association between TB and HIV positivity were variable amongst those studies that reported it, with some finding no significant association [40,58,60,65,73,75] whilst others reported highly significant associations between the two infections, with relative risks of co-infection ranging from 2.0 to 10.75 [51,58]. …”
Section: Resultsmentioning
confidence: 99%
“…Measures of association between TB and HIV positivity were variable amongst those studies that reported it, with some finding no significant association [40,58,60,65,73,75] whilst others reported highly significant associations between the two infections, with relative risks of co-infection ranging from 2.0 to 10.75 [51,58]. …”
Section: Resultsmentioning
confidence: 99%
“…To maximise efficiency and control costs, evidence-based screening tools are needed, 70 but few reports from sub-Saharan Africa have been published to guide how to screen detainees for tuberculosis. The sensitivity and specificity of symptom screening varies depending on the number of symptoms included.…”
Section: Tools Approaches and Structural Interventions To Preventiomentioning
confidence: 99%
“…The sensitivity and specificity of symptom screening varies depending on the number of symptoms included. 27,70 In Zambian detainees, low body-mass index and HIV infection had moderate sensitivity (60%) for tuberculosis. 70 Among South African detainees, the use of chest radiography in addition to symptoms improved screening sensitivity from 24–38% to 70–80%.…”
Section: Tools Approaches and Structural Interventions To Preventiomentioning
confidence: 99%
See 1 more Smart Citation
“…A infecção pelo vírus HIV é um fator que aumenta a vulnerabilidade do acometimento por TB na população em geral. Em indivíduos privados de liberdade, esta infecção apareceu como um fator de risco ainda mais acentuado 16,20,28 . No indivíduo infectado pelo HIV e pelo M. tuberculosis ocorre a aceleração do declínio das funções imunológicas, devido aos patógenos potencializarem-se mutuamente.…”
Section: Discussionunclassified